A new species of the leafhopper genus Apogonalia from Mexico (Insecta: Hemiptera: Cicadellidae: Cicadellini) - Felix, Márcio; Mejdalani, Gabriel (Zootaxa, 2006)
Apogonalia nielsoni, a new cicadelline leafhopper species from Mexico (Nayarit State), is described and illustrated. The color pattern of the new species is similar to that of A. germana (Fowler), whereas the male genital characteristics are similar to those of A. monticola (Fowler). The aedeagal shaft of A. nielsoni has a pair of short, triangular lateral processes that are absent in A. monticola. The paraphyses in both species are formed by a curved, Y-shaped basal plate and by a pair of narrow and very long rami. Apogonalia nielsoni has the arms of the basal plate longer than those of A. monticola. Moreover, the rami of the new species are dorsally or ventrally curved, whereas in the latter species they are approximately straight.